FRI0426 IXEKIZUMAB MAKES REMISSION AND LOW DISEASE ACTIVITY POSSIBLE IN PATIENTS WITH PSORIATIC ARTHRITIS: TWO-YEAR RESULTS IN TNF INADEQUATE RESPONDERS OR BIOLOGIC-NAïVE PATIENTS. (June 2019) - Coates, Laura C.; Ogdie, Alexis; Sunkureddi, Prashanth; Kerr, Lisa; Hufford, Matthew; Helliwell, Philip
Abstract : Background: Psoriatic arthritis (PsA) is a heterogeneous inflammatory disease that can involve peripheral and axial joints, skin, and entheses. A number of validated composite indices have been developed, not only to measure overall disease activity for PsA, but also to provide thresholds for treat-to-target goals. These include MDA (Minimal Disease Activity), DAPSA (Disease Activity in PsA), and PASDAS (PsA Disease Activity Score). We have previously demonstrated that higher proportions of PsA patients treated with ixekizumab (IXE), a monoclonal antibody that selectivity targets interleukin-17A, achieved therapeutic thresholds defined by MDA, DAPSA, and PASDAS versus placebo (PBO) up to Week 24. 1 Objectives: To explore the extent to which IXE can help biologic-naïve and tumor necrosis factor inhibitor (TNFi) inadequate responder patients achieve treat-to-target goals, as defined by composite indices incorporating multiple disease domains, through 108 weeks of treatment. Methods: Data were analyzed from all patients initially randomized to 80 mg IXE every 4 weeks after a 160-mg starting dose in 2 double-blind, PBO-controlled phase III trials investigating the efficacy and safety of IXE. For SPIRIT-P1 (NCT01695239 ), patients (N=107) were bDMARD naïve. For SPIRIT-P2 (NCT02349295 ), patients (N=122) had an inadequate response or were intolerant to TNFis. The following composite measures and definitions were used: MDA and Very Low Disease Activity (VLDA) (see Figure); DAPSA Low Disease Activity (LDA) (≤14 and >4) and remission (≤4); PASDAS LDA/VLDA (≤3.2/≤1.9); and GRACE (GRAppa Composite score) LDA (≤2.3). Modified nonresponder imputation (mNRI; missing data treated as nonresponse for patients discontinued due to lack of efficacy or adverse events; multiple imputation for all other missing data) was used for all analyses. Results: Therapeutic threshold results at Week 108 are summarized in the Figure. Whether measured using MDA, DAPSA, PASDAS, or GRACE, the proportions of IXE-treated patients achieving designated therapeutic thresholds were sustained through 2 years of treatment. Efficacy was similar between SPIRIT-P1 and SPIRIT-P2. Conclusion: High proportions of IXE-treated patients, whether biologic naïve or TNFi inadequate responders, achieved treat-to-target goals, as defined by composite indices incorporating multiple disease domains, through 2 years of treatment. References: [1] Coates L, et al. Ann Rheum Dis. 2018;77(Suppl):A375. Disclosure of Interests: Laura C Coates Grant/research support from: AbbVie, Celgene, Lilly, Novartis and Pfizer, Consultant for: AbbVie, Amgen, BMS, Celgene, Galapagos, Gilead Sciences Inc., Janssen, Lilly, Novartis, Pfizer, Prothena Corp and UCB, Alexis Ogdie Grant/research support from: (To my university) Novartis, Pfizer, Grant/research support from: Novartis, Pfizer, Grant/research support from: Novartis, Pfizer, Grant/research support from: Novartis, Pfizer, Consultant for: AbbVie, Bristol-Myers Squibb, Celgene, Corrona, Eli Lilly and Company, Novartis, Pfizer, and Takeda, Consultant for: AbbVie, Amgen, Bristol-Myers Squibb, Celgene, Corrona, Eli Lilly, Novartis, Pfizer Inc, Takeda, Consultant for: Abbvie, Amgen, BMS, Celgene, Corrona, Lilly, Novartis, Pfizer, Takeda, Consultant for: Abbvie, Amgen, BMS, Celgene, Corrona, Lilly, Novartis, Pfizer, Takeda, Prashanth Sunkureddi Shareholder of: Pfizer, Johnson and Johnson, Mallinckrodt, Regeneron, Grant/research support from: Clinical research trials for Eli Lilly, Novartis, Amgen, Pfizer, Consultant for: Eli Lilly, Novartis, AbbVie, Pfizer, Speakers bureau: Eli Lilly, Novartis, AbbVie, Sanofi Genzyme, Regeneron, Pfizer, Lisa Kerr Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, Matthew Hufford Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, Philip Helliwell Grant/research support from: Paid to charity: from AbbVie, Janssen and Novartis, Consultant for: Paid to charity: from AbbVie, Amgen, Pfizer, and UCB and Celgene. Paid to self: from Celgene and Galapagos